Validitas Kidney Injury Molecule-1 Urin Metode Mikro Enzyme-Linked Immunosorbent Assay Sebagai Penanda Dini Gangguan Ginjal Akut pada Sepsis - Balqis, Lulu Fahrizah; Noormartany, Noormartany; Gondodiputro, Rubin Surachno; Rita, Coriejati (Majalah Kedokteran Bandung, 2016)
Gangguan ginjal akut (GgGA) adalah penurunan fungsi ginjal ditandai peningkatan kreatinin serum ≥0,3 mg/dL atau >1,5 kali dibanding dengan kadar sebelumnya atau penurunan urine output <0,5 mL/jam lebih dari 6 jam. Sepsis merupakan penyebab tersering GgGA (20–50%). Kidney injury molecule-1 (KIM-1) adalah glikoprotein transmembran tipe-1. Kadar KIM-1 urin penderita GgGA akibat sepsis meningkat lebih awal dibanding dengan kreatinin serum. Penelitian bertujuan mengetahui validitas KIM-1 urin sebagai penanda dini GgGA pada sepsis, dilakukan di Rumah Sakit Dr. Hasan Sadikin Bandung periode Februari–Mei 2013. Bentuk penelitian observasional analitik khusus dengan rancangan potong lintang. Subjek penelitian adalah penderita sepsis yang didiagnosis klinisi sesuai kriteria The American College of Chest Physician/The Society of Critical Care Medicine 2001, berdasarkan consecutive admission sampling. Metode yang digunakan mikro enzyme-linked immunosorbent assay. Analisis dengan chi-kuadrat, Mann-Whitney, tabel 2x2, dan kurva receiver operating curve untuk menghitung validitas. Subjek terdiri atas 25 penderita sepsis dengan GgGA dan 25 penderita sepsis tanpa GgGA. Kadar KIM-1 urin penderita sepsis dengan GgGA meningkat dibanding dengan tanpa GgGA. Kadar KIM-1 urine cut-off >0,8 ng/mL memiliki sensitivitas 96%, spesifisitas 60%, nilai duga positif 70,6%, nilai duga negatif 93,8%, dan akurasi 78%. Simpulan, sensitivitas KIM-1 urin tinggi, spesifisitas sedang sehingga dapat digunakan sebagai skrining GgGA pada penderita sepsis. [MKB. 2016;48(1):19–25]Kata kunci: GgGA, KIM-1, sepsis, validitas Validity of Urinary Kidney Injury Molecule-1 Using Micro Enzyme-Linked Immunosorbent Assay Method as an Early Marker of Acute Kidney Injury in Sepsis PatientsAAcute kidney injury (AKI) is a rapid decline in renal function marked by increased serum creatinine of ≥0.3 mg/dL or >1.5 times higher than the previous levels or decreased urine output of <0.5 mL/hour for more than 6 hours. Sepsis is the most common cause of AKI (20–50%). Kidney injury molecule-1 (KIM-1) is a type-1 transmembrane glycoprotein. Urinary KIM-1 levels of sepsis patients due to AKI increases earlier than the serum creatinine levels; thus KIM-1 may serve as an AKI marker. This study aimed to determine the validity of urinary KIM-1 as the early marker in sepsis patients with AKI. The study was a specific observational analytical study with cross-sectional design, conducted in Dr. Hasan Sadikin General Hospital Bandung in February–May 2013. Subjects were patients diagnosed with sepsis by clinicians according to the criteria of the The American College of Chest Physician/The Society of Critical Care Medicine 2001 and were selected by consecutive sampling admissions. Urinary KIM-1 levels were measured by micro enzyme-linked immunosorbent assay. The data were analyzed by chi-square, Mann-Whitney, 2x2 tables, and receiver operating curve to measure validity. Subjects consisted of 25 sepsis patients with AKI and 25 sepsis patients without AKI. Urinary KIM-1 level of sepsis patient with AKI increased compared to patients without AKI. Level of urinary KIM-1 with a cut-off of >0.8 ng/mL presented 96% sensitivity, 60% specificity, 70.6% positive predictive value, 93.8% negative predictive value and 78% accuracy. In conclusion, the level of urinary KIM-1 has high sensitivity and moderate specificity thus can be used for AKI screening in sepsis patients. [MKB. 2016;48(1):19–25]Key words: AKI, KIM-1, sepsis, validity